Improving Students’ Writing Skill of Procedure Text by Using Canva Application - Husni, Na'imatul (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
Media is needed by teachers in supporting teaching in education. Media is a tool used by teachers in teaching, apart from using books or lecture methods, teachers are also expected to have different learning media and adapt the material and conditions to their respective students. Today, technological developments are increasingly rapid and advanced; everyone is expected to understand technology as a support for all existing activities, even in the realm of education. Teachers and students can take advantage of technology-based learning media, one of which is the canva application. Canva is an online-based application that provides attractive designs in the form of templates, features, and the categories provided in it. With various and attractive designs, it makes the learning process not boring. The canva application is used by researchers to assist students in attracting students' interest in learning to write. This research was conducted to find out whether there was a significant effect of using canva on students' ability to write procedural texts. The research procedure includes 5 stages, namely: 1) Pre-test. 2) Introducing students to canva application, its benefits, and procedures for its use, 3) Conducting procedure text learning through canva application, 4) Practicing writing Procedure Text, and 5) Conducting a Post-test. Based on the research, it can be concluded that there is a significant effect of using canva on students' ability to write procedural texts.